Strengthening Religious Tolerance through Islamic Religious Education - Maharani, Adline Syafa; Ahmad, Fathi An-Najmi; Mukhtar, Fitri Alaidza; Ulpah, Maria; Rahayu, Rika; Suhayah, Siti; Hamidah, Wanda (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
In Indonesia’s pluralistic society, Islamic Religious Education (PAI) plays a crucial role in fostering students’ religious tolerance. This study investigates how PAI learning strengthens interreligious tolerance among university students through values of moderation and nonviolence. Using a qualitative approach, six students from different classes and academic years at UIN Sultan Maulana Hasanuddin Banten were interviewed through semi-structured questions. The findings reveal that PAI not only provides theoretical knowledge but also practical experiences, such as discussions, case studies, and group projects, that promote empathy, fairness, and peaceful coexistence. Lecturer guidance, inclusive learning materials, and interactive classroom activities were identified as key factors in internalizing tolerance values. The study suggests that integrating participatory learning, interfaith seminars, and real-life examples of tolerance can further enhance the effectiveness of PAI education in shaping students’ attitudes.